PENDIDIKAN ISLAM MODERAT DAN IMPLIKASINYA PERSPEKTIF KH. ALI MAKSUM - Laksono, Dimas Setiadi; Shohib, Muhammad (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
The escalation of radicalism and intolerance in Indonesia demands a transformation of the educational paradigm capable of bridging the polarization between conservative and liberal religious thought. This study aims to explore the concept of moderate Islamic education from the perspective of KH. Ali Maksum and analyze its implications for the development of the national Islamic education system. Using a qualitative approach with a literature study design, this study examines in-depth the authoritative works of this figure, particularly the book